The spiritual city : theology, spirituality, and the urban - Sheldrake, Philip (Chichester, West Sussex, UK ; Malden, MA : Wiley Blackwell, 2014)
A Spiritual City provides a broad examination of the meaning and importance of cities from a Christian perspective. Contains thought-provoking theological and spiritual reflections on city-making by a leading scholarUnites contemporary thinking about urban space and built environments with the latest in urban theologyAddresses the long-standing anti-urban bias of Christianity and its emphasis on inwardness and pilgrimagePresents an important religious perspective on the potential of cities to create a strong human community and sense of sacred sp.
The city in Christian thought -- Augustine?s two cities -- Monasticism and utopian visions -- The city as sacred -- The city after the reformations -- Michel de Certeau: everyday practices & the city -- Theological reflection and the city -- Place and the sacred -- The art of community -- Reconciliation and hospitality -- Urban virtues -- A spiritual vision of the human city.
Includes bibliographical references and index.
Description based on print version record and CIP data provided by publisher.
Keywords: Cities and towns -- Religious aspects -- Christianity; RELIGION / Christian Life / Social Issues; RELIGION / Christianity / General; Cities and towns -- Religious aspects -- Christianity; Cities and towns -- Religious aspects -- Christianity; City churches; City missions; Electronic books; Electronic books